2017
DOI: 10.1002/ajmg.a.37889
|View full text |Cite
|
Sign up to set email alerts
|

Adams–Oliver syndrome review of the literature: Refining the diagnostic phenotype

Abstract: The Adams-Oliver syndrome (AOS) is defined as aplasia cutis congenita (ACC) with transverse terminal limb defects (TTLD). Frequencies of associated anomalies are not well characterized. Six causative genes have been identified: ARHGAP31, DOCK6, EOGT, RBPJ, NOTCH1, and DLL4. We review 385 previously described individuals (139 non-familial and 246 familial probands and family members) and add clinical data on 13 previously unreported individuals with AOS. In addition to ACC and TTLD, the most commonly associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 22 publications
1
66
0
Order By: Relevance
“…Adams-Oliver syndrome (AOS) is a rare disease that is characterized by defects in the skin and bones of the parietal region and transverse defects of the extremities and is accompanied by vascular abnormalities (Hassed, Li, Mulvihill, Aston, & Palmer, 2017). Although the molecular mechanism including the causative gene ( …”
Section: Adams-oliver Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Adams-Oliver syndrome (AOS) is a rare disease that is characterized by defects in the skin and bones of the parietal region and transverse defects of the extremities and is accompanied by vascular abnormalities (Hassed, Li, Mulvihill, Aston, & Palmer, 2017). Although the molecular mechanism including the causative gene ( …”
Section: Adams-oliver Syndromementioning
confidence: 99%
“…Adams-Oliver syndrome (AOS) is a rare disease that is characterized by defects in the skin and bones of the parietal region and transverse defects of the extremities and is accompanied by vascular abnormalities (Hassed, Li, Mulvihill, Aston, & Palmer, 2017). Although the molecular mechanism including the causative gene(s) of AOS remained unknown for a long time, Notch signaling-related factors, such as NOTCH1 Stittrich et al, 2014), DLL4 (Aminkeng, 2015;Meester et al, 2015), EOGT (Cohen et al, 2014;Shaheen et al, 2013), and RBP-J (Hassed et al, 2012) have recently been reported as the causative genes in this condition.…”
Section: Adams-oliver Syndromementioning
confidence: 99%
“…Adams-Oliver syndrome (AOS) is a developmental disorder characterized by aplasia cutis congenital (a congenital skin defect, typically of the scalp) and transverse limb defects (typically digital amputations) [293,294]. In addition, some AOS patients exhibit nervous system and cardiac/vascular abnormalities.…”
Section: Human Diseases Caused By Rare Mutations In Notch Pathway Genesmentioning
confidence: 99%
“…[3,4] Congenital heart defects (CHDs) are detected in 23% of cases and represent significant morbidity and mortality. [2,5] AOS-related CHDs cover a wide range of severity, predominantly encompassing leftsided obstructive defects, and are often associated with vascular abnormalities, the most frequent of which is cutis marmorata telangiectatica congenita (CMTC). Other vascular defects may impact the lower limb vasculature, portal and cortical renal veins, or the pulmonary vasculature.…”
Section: Clinical Features and Diagnosismentioning
confidence: 99%
“…[7] Abnormalities of the central nervous system (CNS) and structural eye anomalies, for example microphthalmia and retinal vasculopathy, appear more commonly associated with autosomal recessive inheritance. [2,5,8] Developmental delay and seizures each occur in 8-9% of AOS cases overall, but are significantly more frequent (>45%) in patients with microcephaly and are strongly correlated with intracranial vascular defects. [5,9] Additional developmental defects manifesting in <2% of cases include gastrointestinal, renal or reproductive anomalies and facial dysmorphism.…”
Section: Clinical Features and Diagnosismentioning
confidence: 99%